An Experimental Study to the Influence of Fiber Reinforced Polymer (FRP) Confinement on Beams Subjected to Bending and Shear. (2015) - Tudjono, Sri; Lie, Han Ay; Hidayat, Banu Ardi
Abstract: The changing of the Indonesia National Code provision for accommodating the earthquake responses which previously was the SNI 03-1726-2002 to the new SNI 03-1726-2012 had a significant influence to the design criteria of concrete structures. One of the most underlining necessities of this revision was the tsunami and earthquake disasters affecting Indonesia, leading to the differentiation in the earthquake zones used to designing the 2002 SNI code. The newly introduced code has a predominant influence on the amplification of the designed earthquake load. As a consequence, building designed based on the 2002 SNI code requires re-evaluation and strengthening. One method for strengthening concrete structural elements is by using Fiber Reinforced Polymer (FRP) components. Previous research work on short beams loaded in flexure and reinforced with FRP u-shaped shear strengthening around the perimeter of the beam, beneath the slab demonstrated that this reinforcement provided additional strengthening as mandated in the ACI 440 standard. In this study, the combination of FRP flexural and u-shaped shear strengthening in accordance to this ACI 440 is studied to evaluated the enhancement in the capacity of the beam.